Ibn Al-Saiqal Al-Jazari and travel theme in his Makamat - Farhat, Safa Raja (Journal of Humanities & Social Sciences, 2020)
The situation in the Arab environment became disturbed, after the Mongols invaded it. Chaos spread and the scales over turned, which led to the emergence of gangs and bandits and thieves. This chaos led to displacement, for fear of the oppression of these gangs, bearing in mind that those in charge of maintaining security are now commanding their affairs and dealing with them, on the principle of partnership. This is in addition to displacement in search of knowledge and truth, and the impact of these two dimensions has appeared in the Makamat of Ibn Al-Saiqal in their clear form.